When Surgery Goes Wrong: The Importance of the Patient’s Voice - Petrov, Kapka (Operating Room Nurses Association of Canada Journal, 2016)
In 2009, at the age of 33 and in previously excellent health, I woke up with severe right upper abdominal pain on an April night. I ended up in a local hospital, after waiting in the ER for over 9 hours, I was seen by a doctor who dismissed my symptoms and sent me home. A few days later I was feeling very sick and was vomiting and, once again, struggling with excruciating right abdominal pain. I returned to the same hospital. On this visit I was hospitalized due to pancreatitis and for five days I was on IV fluids and narcotic painkillers before having my gallbladder removed laparoscopically. After the surgery I was sent home approximately 6 hours later. I was unable to move, eat, stand, sit or take care of myself and my family.